LEVERAGING EMERGING TECHNOLOGIES TO DEVELOP FUTURE-READY TECHNICAL EDUCATION: A CASE STUDY APPROACH IN LIBRARYAND INFORMATION SCIENCE - Mallik, Soumen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The fast-paced evolution of Library and Information Science (LIS) is causing the integration of emerging technologies, including artificial intelligence, machine learning, blockchain, and augmented reality, providing a significant impact in order for educational programs to remain relevant and impactful in order to prepare the students for the dangers of the future. This systematic review identifies these disruptive technologies and discusses their relevance to Future-ready technical education in LIS. Using a case study approach, this study explores how the technologies are currently integrated into LIS curricula and instructional strategies, while also emphasizing the challenges and opportunities they provide. The study introduces a new approach known as the "Techno-Cognitive Integration Framework" (TCIF), which stresses the importance of cross-disciplinary cooperation in terms of formal technical education, collaborative thinking processes, and experiential development. Educators play a key role in the development of these new learning environments and this framework facilitates innovation, adaptability and lifelong learning for them, and empowers them to integrate new technology in their teaching. Lenker and Kelsey also call for stronger collaboration within the industry and between academia and industry, so that LIS education keeps pace with the evolving technology landscape in our information ecosystem. The paper uses case studies to offer insights into how these technologies can be employed to update LIS education, so students are better prepared for the requirements of a highly technical field. In the end, the results highlight the necessity of building up a LIS workforce that is technologically savvy and educated for the future.